(untitled) (Tanzania Medical Journal, 2020)
Background Warfarin is still the most commonly used oral anticoagulant in many developing countries, including Tanzania. Due to narrow therapeutic window, the safety and effectiveness of warfarin depends on maintaining a tightly controlled International Normalization Ratio (INR), as sub-therapeutic and supra-therapeutic INR levels are associated with thromboembolic and bleeding complications, respectively. However, in Tanzania the clinical and anticoagulation profiles of patients on warfarin have not been well documented. We therefore studied the clinical characteristics, anticoagulation profile and adverse outcomes of patients on warfarin therapy attending the anticoagulation clinic at Muhimbili National hospital (MNH) in Dar es Salaam, Tanzania. Methods This was a hospital-based cross sectional study in which patients attending warfarin anticoagulation clinic for ?3 months were enrolled. Questionnaires and case report forms were used to gather patients’ socio-demographic and clinical characteristics, warfarin use and their most recent INR value. Blood samples were taken and analyzed for current visit INR, full blood count, serum creatinine and albumin levels. Warfarin related complications were obtained through interviews. Associations between INR control levels and warfarin complications with different variables were assessed, and a p-value of < 0.05 was regarded to indicate a significant association. Results In total190 patients fulfilled the inclusion criteria and were enrolled. Their mean ±SD age was 41.3±17.4 years, and 63.2% were females. The most common indication for anticoagulation was mechanical heart valves (71.6%) followed by deep vein thrombosis (18.9%), while atrial fibrillation was an indication in 2.1%. In the total population, INR levels were on-target in only 20.0%, while sub- and supra-therapeutic levels were found in 57.9% and 22.1%, respectively. Bleeding complications were reported in 39 (20.5%) while thromboembolism was present in 6 (3.2%) patients. No significant associations were found between age, gender, renal function, platelet count or serum albumin with INR target levels or presence of warfarin complications. Conclusion Occurrence of complications in about a quarter of this population indicates that the level of warfarin anticoagulation is sub-optimal. Interventions targeting patients, physicians, clinical pharmacists as well as our health systems are needed to optimize warfarin anticoagulation control and reduce complications. Key words: Warfarin, INR, Anticoagulation, Thromboembolic Events, Hemorrhage.